Predictive Ability of the 2-Minute Step Test for Functional Fitness in Older Individuals with Hypertension - Puttipong Poncumhak; Patchareeya Amput; Noppharath Sangkarit; Tichanon Promsrisuk; Arunrat Srithawong (Annals of Geriatric Medicine and Research, 2023)
Background The 2-minute step test (2MST) is a simple and inexpensive functional test that measures an individual's ability to perform continuous stepping up and down on a step platform for two minutes. This study evaluated the 2MST as a tool for assessing functional fitness in older individuals with hypertension and determined the correlation between the 2MST and physical fitness tests. Methods A total of 91 older individuals with hypertension performed physical fitness tests, including the 2MST, 6-minute walk test (6MWT), five times sit-to-stand test (FTSST), grip strength and leg strength assessments, and timed up and go test (TUG) to collectively assess their physical fitness. Results A cutoff score of ≤60 steps in the 2MST had 87.50% sensitivity and 70.59% specificity in predicting functional exercise performance in older individuals with hypertension. Additionally, the number of steps in the 2MST was positively correlated with the distance covered in the 6MWT, isometric grip strength, and isometric leg strength and negatively correlated with the duration of the FTSST and TUG. Conclusions A cutoff score of ≤60 steps in the 2MST predicted functional exercise performance in older individuals with hypertension with 87.50% sensitivity and 70.59% specificity and was correlated with other physical fitness tests, suggesting that the 2MST is a useful tool for assessing functional exercise performance.